1991
DOI: 10.1063/1.460169
|View full text |Cite
|
Sign up to set email alerts
|

The energetics and structure of nickel clusters: Size dependence

Abstract: The energetics of nickel clusters over a broad size range are explored within the context of the many-body potentials obtained via the embedded atom method. Unconstrained local minimum energy configurations are found for single crystal clusters consisting of various truncations of the cube or octahedron, with and without (110) faces, as well as some monotwinnings of these. We also examine multitwinned structures such as icosahedra and various truncations of the decahedron, such as those of Ino and Marks. These… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

20
278
2
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 368 publications
(302 citation statements)
references
References 69 publications
20
278
2
2
Order By: Relevance
“…29 It refers to particularly stable configurations of atoms or molecules. [30][31][32] The molecule-to-molecule spacing, measured at 77 K increased from 6.5 ± 0.5 Å to 7.3 ± 0.3 Å after annealing at approximately 360 K. Together with the observation of triangular holes in the surface and visibly rough steps, this increased spacing supports the proposal that substrate Cu atoms serve as linkers in the networks, thus enabling the formation of a two-dimensional metal-organic coordination network (MOCN). A computational scan of periodic RA gasphase networks versus gas-phase networks of rhodizonate with Cu counterions placed in the interstitial sites showed that the molecule-to-molecule spacing (from the center of the C 6 ring of one molecule to that of the next) within the lowest energy planar RA network that we considered was approximately 7.5-7.6 Å, while that of the rhodizonate/Cu networks was 7.8-7.9 Å.…”
supporting
confidence: 57%
“…29 It refers to particularly stable configurations of atoms or molecules. [30][31][32] The molecule-to-molecule spacing, measured at 77 K increased from 6.5 ± 0.5 Å to 7.3 ± 0.3 Å after annealing at approximately 360 K. Together with the observation of triangular holes in the surface and visibly rough steps, this increased spacing supports the proposal that substrate Cu atoms serve as linkers in the networks, thus enabling the formation of a two-dimensional metal-organic coordination network (MOCN). A computational scan of periodic RA gasphase networks versus gas-phase networks of rhodizonate with Cu counterions placed in the interstitial sites showed that the molecule-to-molecule spacing (from the center of the C 6 ring of one molecule to that of the next) within the lowest energy planar RA network that we considered was approximately 7.5-7.6 Å, while that of the rhodizonate/Cu networks was 7.8-7.9 Å.…”
supporting
confidence: 57%
“…Accordingly, the Au clusters may have Ih or M-Dh structures. But except for the smallest Au clusters, it was shown that the Ih structures are energetically noncompetitive as compared with the M-Dh ones [16,25]. We therefore assume the M-Dh morphology for Au clusters in our experimental size range.…”
mentioning
confidence: 99%
“…At other temperatures, however, the structure with lowest free energy needs to be found. However, perhaps through an expectation that entropic effects are unlikely to be important or are too complicated to take into account, size is usually the only variable that is considered both experimentally [10,11,12] and theoretically [2,3,4,5,6,7,8].In this paper we consider the role that entropy plays in the size evolution of cluster structure, and show that temperature can be a key variable in determining the equi- [14]. These clusters have the optimal shape for the three main types of regular packing seen in clusters: face-centred cubic, icosahedral and decahedral, respectively.…”
mentioning
confidence: 99%